Study of Influence of Continuous Improvement as the Mediator Linking Human Resource Management and Organizational Learning to Operational Performance in Industrial Estates, Pluak Daeng District, Rayong Province - Piwpong , Paradorn; Ramnust, Sumalee (KKBS Journal of Business Administration and Accountancy, 2022)
The objectives of this research are (1) to study the level of human resource management, continuous improvement, organizational learning and the operational performance of the organization in the industrial estate in Pluak Daeng District, Rayong Province, (2) to study the continuous improvement as the mediator linking the human resource management and the operational performance in industrial estates in Pluak Daeng District, Rayong Province and (3) to study the continuous improvement as the mediator linking the organizational learning and the operational performance in industrial estates, Pluak Daeng District, Rayong Province. The questionnaires are used as a tool to collect data from 100 employees at the supervisor level of the organization located in the industrial estate, Pluak Daeng District, Rayong Province according to the concept of Montree Piriyakul (2010). Statistics used in research is the frequency, percentage, mean, standard deviation and structural equation model (SEM) analysis by using Smart PLS 3.0 program. As results, it was showed that (1) organizations in industrial estates, Pluak Daeng District, Rayong Province have a level of continuous improvement, operational performance, human resource management, organizational learning at high overall average. The corresponding values were 4.03, 3.90, 3.70 and 3.66, respectively, (2) the human resource management, organizational learning and continuous improvement directly influence on the operational performance with the values of 0.194, 0.438 and 0.311, respectively. The human resource management and organizational learning have indirectly influence with the values of 0.086 and 0.147, and (3) the human resource management and organizational learning direct influence on continuous improvement with the values of 0.275 and 0.472. The results of this research show that organizations need to manage human resources effectively and need to have the organizational learning in order to continually improve and affect the good operational performance of the organization.